2015
DOI: 10.4040/jkan.2015.45.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silver-Care-Robot Program on Cognitive Function, Depression, and Activities of Daily Living for Institutionalized Elderly People

Abstract: Purpose: The purpose of this study was to identify the effects on cognitive function, depression, and activities of daily living of SilverCare-Robot Program for institutionalized elders. Methods: This study was a nonequivalent control group pretest-posttest design. The participants were 42 institutionalized elders (17 in the experimental group and 25 in the control group). The Silver-Care-Robot Program was provided as an intervention which was conducted twice a week for 5 weeks. The Silver-Care-Robot Program i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 13 publications
(2 reference statements)
2
7
0
Order By: Relevance
“…Analyzing the effect of the RACT on cognitive function improvement showed that the MMSE-DS, SMCQ, and CERAD-K uniformly indicated an improvement, which agreed with previous studies in which robot-assisted, ICT-based cognitive training programs were found effective in reinforcing the different domains of cognitive function [26,37,38].…”
Section: Discussionsupporting
confidence: 88%
“…Analyzing the effect of the RACT on cognitive function improvement showed that the MMSE-DS, SMCQ, and CERAD-K uniformly indicated an improvement, which agreed with previous studies in which robot-assisted, ICT-based cognitive training programs were found effective in reinforcing the different domains of cognitive function [26,37,38].…”
Section: Discussionsupporting
confidence: 88%
“…Six records were excluded because they did not report any outcomes that were directly related to social participation or self-management [61][62][63][64][65][66]. Four records reported on BADLs only [67][68][69][70]. Three studies were excluded because although participants with some form of cognitive impairment were included in the study, the outcomes were not reported separately from outcomes from those who were either cognitively healthy or had other pathologies [71][72][73].…”
Section: Resultsmentioning
confidence: 99%
“…It determined that this population most prefers support for their cognitive functions (38%). Further, in a Korea-based study, Oh et al [24] showed that silver care robots contribute to reducing cognitive deterioration and improving daily living performance. However, the study also highlighted that the elderly engages in limited use of robots’ entertainment functions, and that they experience difficulty directly using and understanding robots.…”
Section: Discussionmentioning
confidence: 99%